2014
DOI: 10.1590/0103-166x2014000400004
|View full text |Cite
|
Sign up to set email alerts
|

Fluência e compreensão da leitura em escolares do 3º ao 5º ano do ensino fundamental

Abstract: Estudos de Psicologia I Campinas I 31(4) I 499-506 I outubro -dezembro 2014 ResumoEste estudo tem como objetivo caracterizar e relacionar a fluência na leitura e a compreensão do texto lido. Participaram da pesquisa 97 escolares do 3º ao 5º ano da rede pública de ensino do município de Marília, São Paulo. Como procedimentos, foram avaliados o tempo de leitura, a prosódia e a compreensão leitora. Foi gravada a leitura oral de um texto e aplicado um teste com questões de múltipla escolha para avaliar a compreen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
1
9
0
9
Order By: Relevance
“…The results indicated that the students´performances were very different from the 3rd to the 5th grades, pointing to a different interaction of the reader with the text, from the beginning of schooling to the later years, a fact also verified by previous studies 11, [21][22][23][24] . Thus, the students from GIII seemed to reach higher levels in that process in relation to GII and this one, in relation to GI.…”
Section: Discussionsupporting
confidence: 70%
“…The results indicated that the students´performances were very different from the 3rd to the 5th grades, pointing to a different interaction of the reader with the text, from the beginning of schooling to the later years, a fact also verified by previous studies 11, [21][22][23][24] . Thus, the students from GIII seemed to reach higher levels in that process in relation to GII and this one, in relation to GI.…”
Section: Discussionsupporting
confidence: 70%
“…The knowledge of the meaning of the word is a variable that expands according to the development, is associated with Cláudia Silva, Franciany B. Pereira social factors and knowledge of the world, and is also influenced by the learning obtained in the school process during literacy teaching. Thus, receptive vocabulary is a reflection of the association between extrinsic factors (related to sociocultural experiences and formal educational learning) and intrinsic factors (associated with the processing of auditory and/or visual information for memory formation) (Martins & Capellini, 2014;Van Dyke et al, 2014;Gray et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that the performance of oral reading and comprehension improves as schooling progresses (13,14) .…”
Section: Discussionmentioning
confidence: 90%